Increasing Educational Awareness Through Community Mentoring in Villages - Saini, Mukhamat; Marlina, Yuli; Nurmawati, Nurmawati; Pujowati, Yenik (STAI Miftahul ULa Nganjuk, 2025)
Sidoharjo Village faces significant challenges in education, including low parental participation in children’s educational activities. The Integrated Competence Community Service Program (KPM-IK) aims to raise educational awareness through training and education-based activities. Using the Asset-Based Community Development (ABCD) approach, this program involves the community in identifying and utilizing local assets to enhance the quality of education. Students collaborate with village residents to plan and implement educational activities, such as training local teachers, conducting awareness campaigns for parents, and establishing learning groups. The results of this community service show a significant increase in community participation in children’s education and the formation of self-sustaining learning groups at the village level. This program successfully created positive change in the community’s awareness of the importance of education.